CUNNING CHARACTERS IN FOLKLORE: A COMPARATIVE NARRATOLOGICAL STUDY OF THE ENGLISH FOX AND THE UZBEK MONKEY - Eshboyeva Dilshoda Utkirovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The trickster is a universal archetype in world folklore, yet its narrative treatment varies significantly across cultures. This article presents a comparative narratological analysis of two animal trickster tales: the English The Fox and the Cat (Joseph Jacobs, 1894) and the Uzbek Maymun va Tulki (The Monkey and the Fox, collected by M. Afzalov, 1965). Using Genette’s categories of order, mood, and voice, as well as Bremond’s logic of narrative sequences, the study examines how each tale structures deception, punishment, and moral resolution. Results show that the English fox fails and dies, reinforcing a pragmatic, individualistic worldview, while the Uzbek monkey succeeds and restores communal justice, reflecting the Central Asian concept of fairness. The findings suggest that the same archetype can encode opposite cultural values depending on narrative structure and focalization. This study contributes to cross-cultural folklore research and narratology by demonstrating how form follows cultural function.